2018
DOI: 10.1371/journal.pone.0203262
|View full text |Cite
|
Sign up to set email alerts
|

“They don’t like us….”: Barriers to antiretroviral and opioid substitution therapy among homeless HIV positive people who inject drugs in Delhi: A mixed method study

Abstract: BackgroundProvision of Anti-Retroviral Therapy (ART) and Opioid Substitution Therapy (OST) are important components of the targeted intervention (TI) programme for people who inject drugs (PWID). Homeless HIV positive PWIDs in Delhi is a key population experiencing gaps in uptake of these services, especially the ART uptake which is reportedly far from 90%, UNAIDS’ 90-90-90 target to end the AIDS epidemic.ObjectiveTo assess the gaps and barriers in accessing the ART and OST services uptake among HIV positive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…94 Comprehensive efforts like these that provide housing alongside harm-reduction programmes and access to HIV and HCV treatment for those who are infected are needed to achieve meaningful reductions in transmission. Expanding access to treatment among homeless PWID should be prioritised given the unique barriers faced by this group, 95 , 96 despite the availability of effective and cost-effective HIV and HCV testing and treatment interventions. 97 , 98 , 99…”
Section: Discussionmentioning
confidence: 99%
“…94 Comprehensive efforts like these that provide housing alongside harm-reduction programmes and access to HIV and HCV treatment for those who are infected are needed to achieve meaningful reductions in transmission. Expanding access to treatment among homeless PWID should be prioritised given the unique barriers faced by this group, 95 , 96 despite the availability of effective and cost-effective HIV and HCV testing and treatment interventions. 97 , 98 , 99…”
Section: Discussionmentioning
confidence: 99%
“…PWID might not seek HIV testing for a variety of reasons including stigma and discrimination [39][40][41][42][43][44], fear of finding out that they are infected, and their perception of being at low risk for HIV infection [38,45]. Moreover, reduced access to HIV testing services or affordable antiretroviral treatment due to insufficient and incorrect knowledge, long waiting time, and lack of family support [46] may be another barrier for PWID to learning their serological status. HIV-infected participants in Aristotle, who knew about their infection, were less likely over the course of the program than the HIV-infected participants who were unaware of their status to report high-risk injection-related behaviors, including daily drug injection, receptive syringe sharing, and especially dividing drugs with a used syringe.…”
Section: Discussionmentioning
confidence: 99%
“…Functional impairment from depression was defined as anyone who said depressive symptoms made it very difficult/extremely difficult for them to work, take care of things at home, or get along with others. Alcohol use was assessed using the Alcohol Use Disorders Identification Test (AUDIT); the score was parameterized into none/mild alcohol use (score ≤7), harmful/hazardous alcohol use (score [8][9][10][11][12][13][14], and alcohol dependence (score ≥15) [22]. Recreational drug use (noninjection and injection) was self-reported using standard measures previously used in India.…”
Section: Study Proceduresmentioning
confidence: 99%
“…India is also home to approximately 2.4 million high-risk MSM, but prevalence of samesex behavior has been reported to be as high as 9% among adult males [6][7][8][9]. Despite an overall decline in HIV prevalence nationally, HIV burden remains high in these 2 groups, who face additional challenges beyond those faced by HIV-infected persons, including criminalization of both behaviors until recently and high levels of provider stigma, which complicate achieving viral suppression [10][11][12]. Furthermore, previous studies have demonstrated high levels of depression, alcohol use, and active substance use in both populations, each of which can independently impact suppression [3,6,[13][14][15].…”
mentioning
confidence: 99%